Authigenic Ferrimagnetic Iron Sulfide Preservation Due to Nonsteady State Diagenesis: A Perspective From Perseverance Drift, Northwestern Weddell Sea. (28th October 2020) - Reilly, Brendan T.; McCormick, Michael L.; Brachfeld, Stefanie A.; Haley, Brian A.
Abstract: We document magnetic mineral diagenesis with high‐resolution magnetic susceptibility, hysteresis, isothermal remanent magnetization, and other rock magnetic measurements through a shallow sulfate‐methane transition (SMT) at Perseverance Drift—a high‐accumulation rate Holocene biosiliceous Antarctic marine sediment deposit. The structure of the SMT is defined with porewater measurements from the same core, allowing direct comparison. Dissolution of the detrital (titano)magnetite assemblage, with preferential dissolution of stochiometric magnetite, occurs in the upper SMT. Higher coercivity magnetic minerals dissolve more slowly, continuing to dissolve through the entire SMT and could be a source of ferric iron for microbial respiration following exhaustion of porewater sulfate, as suggested by accumulation of porewater ferrous iron below the SMT. Superparamagnetic ferrimagnetic mineral enrichment/depletion occurs in three phases through the SMT and is coupled tightly to the availability of dissolved ferrous iron relative to dissolved sulfide. High concentrations of authigenic remanence‐bearing iron sulfides, including greigite and hexagonal 3C pyrrhotite, which can be detected using remanence parameters but not in‐field concentration dependent parameters, accumulate in a transient horizon at the base of the SMT during this early diagenesis, where sulfide is present but limited relative to dissolved ferrous iron. Formation of this remanence‐bearing iron sulfide horizon is likely facilitated by continued iron reduction through the SMT. Nonsteady state perturbations that shift the porewater profile, such as changes in carbon flux or sedimentation rate, can lead to preservation of these transient horizons, much like well documented preservation of manganese oxide layers in marine sediments following similar shifts to porewater profiles. Key Points: Magnetic mineral diagenesis is studied in Antarctic sediments using high‐resolution porewater and rock magnetic data Magnetic mineral dissolution and authigenesis is tightly coupled to dissolved sulfide and ferrous iron concentrations Remanence‐bearing iron sulfides form below the sulfate‐methane transition and can be preserved following nonsteady state diagenesis